Desvio de conduta: um estudo exploratório sobre atitudes antiéticas de empregados do setor industrial - Assad, Marta Maria Nogueira (2007)
This work approaches some of the behaviors revealed by the industrial employees from the region of the medium Vale do Paraíba, State of São Paulo, which can be characterized as behavior deviation inside the organization, because they are in disagreement with the internal codes – implicit or explicit ones – and that result in losses for the organization. The research aims at identifying its decisive and significant factors. This is an exploratory study which uses the questionnaire technique, applied to a sample of 1.450 employees, and the interview as well. The statistic pattern utilized to determine the behavior deviation incidence, submitted to the evaluation, has been considered useful for the deviation foresight. Among the results are the identification of the behavior deviation incidence, with 63% of occurrence related to the amount of the 936 participators that returned valid questionnaires; the identification of the decisive factors – the organizational and ethical environment, the subjective and the economic factors –; and the proposal of a cycle that represents the dynamics that guides the behavior deviation and its determiners that encloses the following steps: the decisive factor, the occurrence of the behavior deviation, the losses for organization-employee, the feedback of the process. The participators profile is related to the behavior deviation issue, according to their instruction level and their work area. The results obtained with the interviews have pointed that employees of the enterprises considered in this research are involved in extra activities, usually to complement their wages. There is a disconnection between employee and employer, what can suggest communication failures and inadequacy of behaviors codes and rules; there is a culture of the behavior deviation. The research has pointed that: (1) it is possible to use that cycle to identify and predict the behavior deviation, since this behavior is considered conflicting with the enterprise interests; (2) the organizational culture may be incorporated in order to develop the ethical behaviors of the employees and consequent competitive advantages for the organization; (3) it is necessary to create a planning process that regards all the involved social actors, having as basis the ethical principles applied to the behaviors codes formation, in order to encourage the development of the character values.